Akibat Hukum Perjanjian Hutang Piutang dengan Persyaratan Dokumen Palsu (Studi Kasus Pengadilan Negeri Denpasar) - Putu Dila Parmila; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Fakultas Hukum, Universitas Warmadewa, 2020)
Corruption has become an extraordinary crime, because its existence greatly affects economic growth in Indonesia. There are many factors that influence the criminal acts of corruption to occur; usually because the perpetrator has the authority so it is very easy to carry out the action. There are many ways to carry out this corruption, one of which is by falsifying documents that are used as conditions for conducting debt-receivables agreements. The objects that this research examines are the legal consequences of the accounts payable agreement with the requirements for false documents and the factors of the occurrence of the accounts payable agreement with false document requirements and settlement flow. The method used to examine these two issues is the normative legal research method. Based on the results of data analysis, it was found that: disbursement of funds resulting from falsification of data or documents indicated that the defendant would not be convicted of the forgery article, but was charged with committing a criminal act of corruption because the result of his action was loss of state assets; The main factor affecting the occurrence of a criminal act of corruption is the bad faith of the defendant himself and also from the factor of authority he is being granted, so that he can make use of the opportunity to carry out his actions.